Fight or flight : starring Falcon - Wyatt, Chris, 1975- (Mighty Marvel chapter book., 2017)
While the Avengers are chasing Thanos through the galaxy, Falcon monitors Earth from Avengers Tower. When Ultron strikes, Falcon leads Quicksilver, Scarlet Witch, Vision, Black Widow, and Hawkeye in battle but things go awry and Hawkeye is kidnapped. Falcon begins to doubt his leadership abilities, but he finds the inspiration to pull the team together and rescue Hawkeye.